ANALYSIS OF ARTISTIC DETAILS OF UKRAINIAN COSTUME ON THE BASIS OF THE CREATIVE JOURNEY OF DOMINIC DE LA FLISE - Паранько, Н. П. (Art and Design, 2018)
Research of artistic and compositional characteristics of the folk costume on the basis of the structural analysis of the creative heritage of the researcher Dominique dela Flise for their further use in the design of modern clothing. The research uses a literary and analytical, system and structural analysis of the form, decoration and color range of the Ukrainian women's outerwear. The conducted researches make it possible to identify the most characteristic structural, artistic and compositional features of the formation and coloring of Ukrainian suits and skirts in order to design promising forms of modern outerwear of the autumn-spring type. For the first time a scientific analysis and systematization of compositional characteristics of a variety of forms, decoration and colouristics of women's suits and skirts were conducted on the basis of studying and structuring of the original documents from the creative heritage of the researcher of the Ukrainian folk culture, Dominique Pierre dela Flise. The research results presented will be used in designing modern fashion models based on Ukrainian folk costume